2017
DOI: 10.1098/rsbl.2017.0375
|View full text |Cite
|
Sign up to set email alerts
|

Colour and luminance contrasts predict the human detection of natural stimuli in complex visual environments

Abstract: Much of what we know about human colour perception has come from psychophysical studies conducted in tightly-controlled laboratory settings. An enduring challenge, however, lies in extrapolating this knowledge to the noisy conditions that characterize our actual visual experience. Here we combine statistical models of visual perception with empirical data to explore how chromatic (hue/saturation) and achromatic (luminant) information underpins the detection and classification of stimuli in a complex forest env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The perception of visual contrast is a combination of spatial (relative size and position of colour pattern elements), chromatic (hue and saturation), and achromatic (luminance) properties of a colour pattern due to lower and higher level neuronal processing of visual information (e.g. Pearson & Kingdom, ; Shapley & Hawken, ; Simmons & Kingdom, ; White et al, ; Willis & Anderson, ). Furthermore, interactions between the absolute and relative size of colour pattern elements and their chromatic and achromatic properties includes simultaneous colour contrast and colour constancy mechanisms that are understood in very few visual systems (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The perception of visual contrast is a combination of spatial (relative size and position of colour pattern elements), chromatic (hue and saturation), and achromatic (luminance) properties of a colour pattern due to lower and higher level neuronal processing of visual information (e.g. Pearson & Kingdom, ; Shapley & Hawken, ; Simmons & Kingdom, ; White et al, ; Willis & Anderson, ). Furthermore, interactions between the absolute and relative size of colour pattern elements and their chromatic and achromatic properties includes simultaneous colour contrast and colour constancy mechanisms that are understood in very few visual systems (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Admittedly, our approach is limited, as it does not provide information from the ultraviolet spectrum, which is known to be used by multiple bird lineages in the context of foraging (Cronin, Johnsen, Marshall, & Warrant, 2014;Cuthill et al, 2000), and only superficially incorporates predator perception of frog and model colours. We do not expect the former to misguide our conclusions considerably, since previous studies have found that neither painted paraffin (Rojas, Stow, AmĂ©zquita, SimĂ”es, & Lima, 2015;White, Rojas, Mappes, Rautiala, & Kemp, 2017) nor most studied dendrobatid frogs reflect in the ultraviolet spectrum (Dreher, Cummings, & Pröhl, 2015;Preißler & Pröhl, 2017;Rojas et al, 2015;Summers, Cronin, & Kennedy, 2003). The latter could be more misleading, as we cannot fully evaluate whether the predators attacking our models are able to differentiate between their colours, or whether they see the red and yellow models as two categorically distinct sets,…”
Section: Field Experimentsmentioning
confidence: 75%
“…Given that the chromatic and achromatic patterns are different and almost complementary we suggest that the chromatic and achromatic components of colour patterns could be used for different functions, such as sexual selection, species recognition, or defense. Chromaticity and luminance are processed independently, and there is variation in their relative importance in stimulus choice and discrimination, among many species including crabs, psyllids, honeybees, bumblebees, flies, hawkmoths, birds and humans (Baldwin & Johnsen, ; Dyer et al., ; Farnier, Dyer, & Steinbauer, ; Giurfa, Vorobyev, Brandt, Posner, & Menzel, ; Keil, Miskovic, Gray, & Martinovic, ; Kelber, , ; Osorio & Vorobyev, ; White & Kemp, , 2017; White, Rojas, Mappes, Rautiala, & Kemp, ; Zhou, Ji, Gong, Gong, & Liu, ). This suggests that chromatic and achromatic channels could have different functions in any taxa.…”
Section: Examples and Their Implicationsmentioning
confidence: 99%